Analysis of distribution patterns of selected ephemeral wetland species in Western Pomerania (NW Poland, NE Germany) - Popiela, Agnieszka; Nalepka, Dorota; Łysko, Andrzej (Biodiversity: Research and Conservation, 2011)
Phytogeographical conditions of the occurrence of 13 selected ephemeral wetland species of the Isoëto-Nanojuncetea class in Western Pomerania are analysed and discussed on the basis of distribution in Western Pomerania (maps are provided), distribution in Europe, general distribution range, taxonomic relations and palynological data. Present distribution patterns of the analysed taxa in Western Pomerania can thus be permanent not for a very long time and reflect the history of the settling of Pomerania by these species.